Contextual Facilitators of and Barriers to Nursing Home Pressure Ulcer Prevention. (May 2016) - Hartmann, Christine W.; Solomon, Jeffrey; Palmer, Jennifer A.; Lukas, Carol VanDeusen
Abstract : PURPOSE: To present findings of a study of institutional factors related to pressure ulcer (PrU) prevention in Veterans Health Administration nursing homes. TARGET AUDIENCE: This continuing education activity is intended for physicians and nurses with an interest in skin and wound care. OBJECTIVES: After participating in this educational activity, the participant should be better able to: 1. Identify the study's design, process, and purpose. 2. List the factors pertaining to sites with improving performance. ABSTRACT: OBJECTIVE: Important gaps exist in the knowledge of how to achieve successful, sustained prevention of pressure ulcers (PrUs) in nursing homes. This study aimed to address those gaps by comparing nursing leadership and indirect care staff members' impressions about the context of PrU prevention in facilities with improving and declining PrU rates. SETTING: The study was conducted in a sample of 6 Veterans Health Administration nursing homes (known as community living centers) purposively selected to represent a range of PrU care performance. DESIGN AND PARTICIPANTS: One-time 30-minute semistructured interviews with 23 community living center staff were conducted. Qualitative interview data were analyzed using an analytic framework containing ( a ) a priori analytic constructs based on the study's conceptual framework and ( b ) sections for emerging constructs. MAIN RESULTS: Analysis revealed 6 key concepts differentiating sites with improving and declining PrU care performance. These concepts were (1) structures through which the change effort is initiated; (2) organizational prioritization, alignment, and support; (3) improvement culture; (4) clarity of roles and responsibilities; (5) communication strategies; and (6) staffing and clinical practices. Results also pointed to potential contextual facilitators of and barriers to successful PrU prevention. CONCLUSIONS: Leadership's visible prioritization of and support for PrU prevention and the initiation of PrU prevention activities through formal structures were the most striking components represented at sites with improving performance, but not at ones where performance declined. Sites with improving performance were more likely to align frontline staff and leadership goals for PrU prevention.